ErbB2/HER2 receptor tyrosine kinase regulates human papillomavirus promoter activity - Mikuličić, Snježana; Shamun, Merha; Massenberg, Annika; Franke, Anna-Lena; Freitag, Kirsten; Döring, Tatjana; Strunk, Johannes; Tenzer, Stefan; Lang, Thorsten; Florin, Luise (Frontiers in Immunology, 2024)
Human papillomaviruses (HPVs) are a major cause of cancer. While surgical intervention remains effective for a majority of HPV-caused cancers, the urgent need for medical treatments targeting HPV-infected cells persists. The pivotal early genes E6 and E7, which are under the control of the viral genome's long control region (LCR), play a crucial role in infection and HPV-induced oncogenesis, as well as immune evasion. In this study, proteomic analysis of endosomes uncovered the co-internalization of ErbB2 receptor tyrosine kinase, also called HER2/neu, with HPV16 particles from the plasma membrane. Although ErbB2 overexpression has been associated with cervical cancer, its influence on HPV infection stages was previously unknown. Therefore, we investigated the role of ErbB2 in HPV infection, focusing on HPV16. Through siRNA-mediated knockdown and pharmacological inhibition studies, we found that HPV16 entry is independent of ErbB2. Instead, our signal transduction and promoter assays unveiled a concentration-and activation-dependent regulatory role of ErbB2 on the HPV16 LCR by supporting viral promoter activity. We also found that ErbB2's nuclear localization signal was not essential for LCR activity, but rather the cellular ErbB2 protein level and activation status that were inhibited by tucatinib and CP-724714. These ErbB2-specific tyrosine kinase inhibitors as well as ErbB2 depletion significantly influenced the downstream Akt and ERK signaling pathways and LCR activity. Experiments encompassing low-risk HPV11 and high-risk HPV18 LCRs uncovered, beyond HPV16, the importance of ErbB2 in the general regulation of the HPV early promoter. Expanding our investigation to directly assess the impact of ErbB2 on viral gene expression, quantitative analysis of E6 and E7 transcript levels in HPV16 and HPV18 transformed cell lines unveiled a noteworthy decrease in oncogene expression following ErbB2 depletion, concomitant with the downregulation of Akt and ERK signaling pathways. In light of these findings, we propose that ErbB2 holds promise as potential target for treating HPV infections and HPV-associated malignancies by silencing viral gene expression.